Windows Netbooks The Path to Low-Cost Computing - Kelly, James Floyd (Apress, 2013)
If you’ve never used a laptop before, the netbook’s size and weight might not be as big a shock to you as it is to those of us who’ve had to lug around one of its larger cousins. The screen sizes, however, might come as a shock (probably to anyone under age 25). The screens are small. Sizes typically range from seven inches to 11 inches (measured diagonally). Most netbook displays support extremely fine resolutions, but again, you’ll be in a much better position to judge what you need by finding a local netbook seller and examining, not just a given netbook’s weight and screen size/resolution, but all of the features described in this chapter